Risks and benefits of energy systems : proceedings of an International Symposium on the Risks and Benefits of Energy Systems - International Symposium on the Risks and Benefits of Energy Systems (1984 : Julich, Germany); International Atomic Energy Agency; World Health Organization; United Nations Environment Programme (Vienna : International Atomic Energy Agency, 1984)
18